Molecular basis of AvrXa7 mediated virulence in bacterial blight of rice - Antony, Ginny (Kansas State University, 2010)
Plants have evolved sophisticated mechanisms to protect against microbial invaders of which resistance (R) genes are an important component. R genes mediate specific recognition of pathogens possessing cognate avirulence (avr) gene products, which leads to the induction of plant defense responses and the arrest of pathogen ingress. In contrast to numerous examples of R gene–avr interactions, the susceptible interaction is less well examined. Recent studies on rice and wheat indicate that host resistance to pathogens also involves genetic variability in dominant traits for susceptibility. Xanthomonas oryzae pv.oryzae (Xoo) causes bacterial blight disease in rice, a serious threat in the major rice growing regions of Asia. The pathogenicity of Xoo depends on the translocation of a cocktail of effector proteins into rice cells by a type III secretion system. The family of transcription activator like (TAL) effectors is the one of the most intriguing due to their eukaryotic features and function as major virulence determinants. The specificity of TAL effectors is determined by the nearly identical repeat units at the center of each protein. The major virulence determinant of the strain PXO99A is PthXo1, which hijacks the transcription of the host susceptibility (S) gene Os8N3, an allele of recessive resistance gene xa13. The strains that overcome xa13-mediated resistance harbor alternate major TAL effectors including PthXo2, PthXo3 and AvrXa7. Alternate effectors do not induce Os8N3. This study identified the alternate S gene Os11N3, which is dependent on the effectors AvrXa7 and PthXo3. The effectors bind to specific elements in the proximal promoter regions of the respective S genes and act as transcriptional activators. Our results indicate that rice–Xoo interactions involve gene-for-gene susceptibility to bacterial blight in addition to gene-for-gene resistance.
Keywords: AvrXa7; Os11N3; Susceptibility gene; Recessive resistance; xa5; Bacterial blight Rice; Agriculture, Plant Pathology (0480)